Biosynthesis of cell wall mannan in the conidium and the mycelium of Aspergillusfumigatus. (11th October 2016) - Henry, Christine; Fontaine, Thierry; Heddergott, Christoph; Robinet, Pauline; Aimanianda, Vishukumar; Beau, Remi; Beauvais, Anne; Mouyna, Isabelle; Prevost, Marie‐Christine; Fekkar, Arnaud; Zhao, Yanan; Perlin, David; et al.
Abstract: The galactomannan is a major cell wall molecule of Aspergillus fumigatus . This molecule is composed of a linear mannan with a repeating unit composed of four α1, 6 and α1, 2 linked mannose with side chains of galactofuran. To obtain a better understanding of the mannan biosynthesis in A. fumigatus, it was decided to undertake the successive deletion of the 11 genes which are putative orthologs of the mannosyltransferases responsible for establishing α1, 6 and α1, 2 mannose linkages in yeast. These deletions did not lead to a reduction of the mannan content of the cell wall of the mycelium of A. fumigatus . In contrast, the mannan content of the conidial cell wall was reduced and this reduction was associated with a partial disorganization of the cell wall leading to defects in conidial survival both in vitro and in vivo. Abstract : This article is part of aspecial issue on Fungal Cell Wall, edited by Neil Gow and Elizabeth Hartland.